Assessing the transition of municipal solid waste management using combined material flow analysis and life cycle assessment - Wang, Dan; He, Jun; Tang, Yu-Ting (Springer, 2020)
Faced with the challenges to deal with increasingly growing and ever diversified municipal solid waste (MSW), a series of waste directives have been published by European Commission to divert MSW from landfills to more sustainable management options. The presented study assessed the transition of MSW man-agement in Nottingham, UK, since the enforcement of the EU Landfill Directive using a tool of combined materials flow analysis (MFA) and life cycle assess-ment (LCA). The results show that the MSW management system in Nottingham changed from a relatively simple landfill & energy from waste (EfW) mode to a complex, multi-technology mode. Improvements in waste reduction, material re-cycling, energy recovery, and landfill prevention have been made. As a positive result, the global warming potential (GWP) of the MSW management system re-duced from 1,076.0 kg CO2–eq./t of MSW in 2001/02 to 211.3 kg CO2–eq./t of MSW in 2016/17. Based on the results of MFA and LCA, recommendations on separating food waste and textile at source and updating treatment technologies are made for future improvement.